PLASMA HOMOCYSTEINE IN PATIENTS OF MIGRAINE WITHOUT AURA - Bokhari, Faraz Ahmed; Shakoori, Tania A.; Hassan, Syed Ahmad A.; Qureshi, Hamid J.; Qureshi, Ghulam A. (Journal of Ayub Medical College Abbottabad, 2010)
Background: Few studies have studied the role of homocysteine in migraineurs and have produced conflicting results. The MTHFR C677T genotype has been associated with increased risk of migraine in selected clinical samples. We assessed the association of the MTHFR C677T variant with migraine, the corresponding homocysteine levels and their correlation. Method: We studied 27 random adult migraineurs with aura (MWA), migraine without aura (MWOA), and 32 non-migraineurs (controls) from Lahore, Pakistan in this pilot study which is still under progress. Results: We found significant differences in homocysteine levels between various diagnostic groups (K-W test: p=0.005). One-way ANOVA, post-hoc tests revealed significant differences in homocysteine levels between Nonmigraineurs, MWA (p=0.002, CI: 1.93 - 9.19) and MWoA (p=0.002, CI: -9.19 - -1.9). We found a significant association between the migraine group and C677T-MTHFR variant mutant allele (C/T) (p=0.039). We did not find a significant association between C677T-MTHFR variant and homocysteine levels. Conclusion: In this pilot study, we found plasma homocysteine levels to be significantly associated with MWOA. Additionally, plasma homocysteine levels were lower in MWA than in MWOA. Furthermore, we did not find a relationship between homocysteine levels and the MTHFR variant (SNP rs1801133). Lastly, there may be a relationship between the MTHFR variant (SNP rs1801133) and migraine in this population. Keywords: Plasma homocysteine, Migraine